American heart [compact disc] - Boone, Benson, 2002- (Warner Records, 2025)
Benson Boone is quickly soaring to global pop stardom on the heels of a breakout year in 2024. His brand-new album American Heart builds upon that success and expands his sonic landscape, creating a project that feels both larger-than-life and sincere at its core.